Software Architecture : 9th European Conference, ECSA 2015, Dubrovnik/Cavtat, Croatia, September 7-11, 2015. Proceedings - Weyns, Danny; Mirandola, Raffaela; Crnkovic, Ivica; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 9th European Conference on Software Architecture, ECSA 2015, held in Cavtat, Croatia in September 2015. The 12 full papers and 15 short papers presented together with three education and training papers in this volume were carefully reviewed and selected from 100 submissions. They are organized in topical sections named: adaptation; design approaches; decisions and social aspects; education and training; cloud and green; agile and smart systems; analysis and automation; services and ecosystems. .
Adaptation -- Design approaches -- Decisions and social aspects -- Education and Training -- Cloud and green -- Agile and smart Systems -- Analysis and automation -- Services and ecosystems.
Keywords: Software engineering; Information Systems; Computer science; Software Engineering; Management of Computing and Information Systems; Programming Languages, Compilers, Interpreters; Information Systems Applications (incl. Internet).